2016
DOI: 10.1371/journal.pone.0154388
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Delivery and Satisfaction among Indigenous and Poor Women in Guatemala, Mexico, and Panama

Abstract: Indigenous women in Mesoamerica experience disproportionately high maternal mortality rates and are less likely to have institutional deliveries. Identifying correlates of institutional delivery, and satisfaction with institutional deliveries, may help improve facility utilization and health outcomes in this population. We used baseline surveys from the Salud Mesoamérica Initiative to analyze data from 10,895 indigenous and non-indigenous women in Guatemala and Mexico (Chiapas State) and indigenous women in Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
26
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
9
26
1
1
Order By: Relevance
“…A study conducted in public health facilities of Kenya states that more than half (51.7%) were multiparous where as in this study 35% were multiparous. A tri-nation study states that decision regarding utilization of birthing facilities is often made by the husband or his family members rather than by the parturient woman [13] where as another study of eastern Nepal showed that slightly more than half of the of decision for delivery point were made by mother and her spouse which is also considered as supporting details to this study. [33] The reason behind this could be because of the patriarchal nature of society, where the nal decision are mostly made by the husbands or elder persons of the household regarding delivery point.…”
Section: Satisfaction On Institution Delivery Servicessupporting
confidence: 58%
See 1 more Smart Citation
“…A study conducted in public health facilities of Kenya states that more than half (51.7%) were multiparous where as in this study 35% were multiparous. A tri-nation study states that decision regarding utilization of birthing facilities is often made by the husband or his family members rather than by the parturient woman [13] where as another study of eastern Nepal showed that slightly more than half of the of decision for delivery point were made by mother and her spouse which is also considered as supporting details to this study. [33] The reason behind this could be because of the patriarchal nature of society, where the nal decision are mostly made by the husbands or elder persons of the household regarding delivery point.…”
Section: Satisfaction On Institution Delivery Servicessupporting
confidence: 58%
“…They are delay in seeking care, delay in reaching care and delay in receiving care. Poor birth preparedness, knowledge on institution delivery, family in uence on decision, geographical inaccessibility, and unmet needs of care in CEONC and fear of hospital setting [13] are common factors related to rst delay. Late and poor-quality referral, transport not available and inadequate decisions by husband/relatives have been associated with the second type of delay.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery care is cost-free in government-managed facilities. Midwifery is legal, with a substantial proportion of deliveries attended by midwives in poor areas of Guatemala (Colombara et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Women who have sufficient knowledge about delivery danger signs might have perceived service benefits of a health institution, like complication management by skilled health care workers in time of labor. Haiti service provision assessment survey who attend primary in rural Haiti(AOR=1.47),who attend secondary and above in rural Haiti(AOR=2.06)[47], who attend secondary & above in Guatemala,Mexco and panama(AOR=1.36)[52], an analysis from Bangladesh Demographic Health Survey 2011 who attend Primary school(AOR=1.264), Secondary & .783) than mothers with inadequate exposure. This finding was supported by a primary cross sectional study in a remote mountains district of Nepal[56].…”
mentioning
confidence: 99%